Skull of the grey heron (Ardea cinerea ): detailed investigation of the orbital region - Bavdek, S.V.; Golob, Z.; Janžekovič, F.; Rutland, Catrin S.; Kubale, V. (Wiley, 2017)
The skull of the grey heron (Ardea cinerea) was examined with an emphasis on describing the orbital region. In the young (circa sixteen to seventeen days old) heron, the frontal bone (os frontale) and nasal bone (os nasale) comprised separate paired bones, connected by sutures (sutura interfrontalis, sutura internasalis and sutura frontonasalis plana). In adult animals, the relationship between these bones was different: the left and right frontal bone and the left and right nasal bone had grown together, and the frontal bone and nasal bone had fused into a common frontonasal bone (os frontonasale). In the ectethmoid bone (os ectethmoidale), the main components comprised of the orbital and antorbital part of the ectethmoid plate (lamina ectethmoidalis orbitalis et antorbitalis), the lateral process (processus lateralis ectethmoidalis) and the tubercle (tuberculum ectethmoidalis); the left and right ectethmoid plates were fused together to form the ectethmoid sinus (sinus ectethmoidalis) between them. In the young heron, the anatomical and functional link between the frontal and lacrimal bones did not exist yet, nor did the osseous frame of the ectethmoid-lacrimal complex. Further research into the young heron skulls is needed. This article provides novel insights into the grey heron's orbital region.